What Is Special About the “Create” Activity on RADEC? Student Creative Product Description - Sutinah, Cucun; Ruqoyyah, Siti; Kusumastuti, Fransiska Astri (KnE Social Sciences, 2025)
In teacher education, especially in the artistic fields like dance, developing creativity is essential. This study explore the impact of the read, answer, discuss, explain, and create (RADEC) learning model on the creativity of prospective elementary school teachers in creating dance. Using an explanatory mixed-methods approach, the study examined how the RADEC model influenced students’ creativity and the creative dance produced. Seventy-three students from the Primary School Teacher Education program at IKIP Siliwangi participated. Data were collected through a creative thinking test, observation sheets, and a creativity assessment rubric, and were then analyzed descriptively. The results showed that the RADEC model significantly enhanced students’ creativity, with the “create” phase being particularly effective. The students’ dance products met the expected creativity criteria. This study highlights the importance of applying the RADEC model in teacher education to better prepare students for teaching and creating innovative art.